Pathomechanism Heterogeneity in the Amyotrophic Lateral Sclerosis and Frontotemporal Dementia Disease Spectrum: Providing Focus Through the Lens of Autophagy. Issue 8 (3rd April 2020) - Casterton, Rebecca L.; Hunt, Rachel J.; Fanto, Manolis
Abstract: Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) constitute aggressive neurodegenerative pathologies that lead to the progressive degeneration of upper and lower motor neurons and of neocortical areas, respectively. In the past decade, the identification of several genes that cause these disorders indicated that the two diseases overlap in a multifaceted spectrum of conditions. The autophagy-lysosome system has been identified as a main intersection for the onset and progression of neurodegeneration in ALS/FTD. Genetic evidence has revealed that several genes with a mechanistic role at different stages of the autophagy process are mutated in patients with ALS/FTD. Moreover, the three main proteins aggregating in ALS/FTD, including in sporadic cases, are also targeted by autophagy and affect this process. Here, we examine the varied dysfunctions and degrees of involvement of the autophagy-lysosome system that have been discovered in ALS/FTD. We argue that these findings shed light on the pathological mechanisms in the ALS/FTD spectrum and conclude that they have important consequences both for treatment options and for the basic biomolecular understanding of how this process intersects with RNA metabolism, the other major cellular process reported to be dysfunctional in part of the ALS/FTD spectrum. Graphical abstract: Image 1 Highlights: Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) form a continuum spectrum of aggressive neurodegenerative diseases. Several genes mutated in ALS/FTD regulate the autophagy-lysosome system. Autophagy regulates the degradation of the key proteins that aggregate in ALS/FTD. A future challenge is the full understanding of the interplay between autophagy and RNA dysfunctions.